2003
DOI: 10.1142/s0217979203018417
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Adsorption on Clean and Oxygen Covered Flat and Stepped Ag(001)

Abstract: In the present paper we review our findings on ethylene adsorption on clean and oxygen covered Ag(001) surfaces investigated by dosing the gas with a Supersonic Molecular Beam and analysing the adsorption state either by High Resolution Electron Energy Loss Spectroscopy or by High Resolution X Rays Photoemission Spectroscopy. The final adsorption state depends on the translational and on the internal energy of the gas-phase molecules and on the presence of defects. At low translational energy ethylene either p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
4
11
0
Order By: Relevance
“…Ethylene adsorption at Ag surfaces [3,4] is particularly important for the understanding of the so-far unsolved ethylene epoxidation reaction [5][6][7][8] for which surface defects might play a pivotal role. This paper follows our previous investigations of C 2 H 4 adsorption on Ag(100) and Ag(410) [9][10][11][12][13][14][15]. In these experiments we demonstrated that physisorbed and π-bonded states exist on Ag(100) and are characterized by a different adsorption energy [9] and by a different C 1s photoemission signature [11].…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Ethylene adsorption at Ag surfaces [3,4] is particularly important for the understanding of the so-far unsolved ethylene epoxidation reaction [5][6][7][8] for which surface defects might play a pivotal role. This paper follows our previous investigations of C 2 H 4 adsorption on Ag(100) and Ag(410) [9][10][11][12][13][14][15]. In these experiments we demonstrated that physisorbed and π-bonded states exist on Ag(100) and are characterized by a different adsorption energy [9] and by a different C 1s photoemission signature [11].…”
Section: Introductionsupporting
confidence: 83%
“…A less strongly bound moiety, metastable at the temperature of the experiment, appears only at higher coverage. Preliminary data on the C 2 H 4 interaction with Ag(210) were reported briefly in previous papers [14,15] and are completed by the present, detailed, report on energy, angle and coverage dependence of the sticking probability.…”
Section: Introductionmentioning
confidence: 78%
“…7 0.08 ML of Br/Cl was thereby found to shift the ethene desorption peak in TPD to 132 K. A stabilization of ethene adsorption at undercoordinated atoms was found also at Ag surfaces, possibly providing a mechanism for the relatively high desorption temperatures observed experimentally ͑about 140 K͒. 28,40,43 The stabilization of ethene on less defined rough copper surfaces was previously reported by thermal desorption spectroscopy by Otto and co-workers 30,31 who found a broad desorption peak of ethene at around 210 K in agreement with our findings. Their spectra also show that the wagging mode 7 / 8 remains nearly unshifted compared to ethene on Cu͑111͒, as indicated in Table I.…”
Section: Stabilization Of Ethenementioning
confidence: 86%
“…A further point to be clarified is the role of oxygen in stabilizing and promoting ethylene adsorption on Ag(100) ( [424] and references therein). The desorption temperature of ethylene on Ag (100) in presence of oxygen is close to the one measured on bare stepped Ag surfaces, i.e.…”
Section: Dissociative Chemisorption: Methane On Stepped Pt and Ni Surmentioning
confidence: 99%